SOSOK RATU ADIL DALAM RAMALAN JAYABAYA - Fatkhan, Muh (Refleksi: Jurnal Filsafat dan Pemikiran Islam, 2019)
The doctrine of Ratu Adil or messias is actually not something new. In various cultures and social institutions, this kind of doctrine is often found, both within a religious framework and within a particular cultural framework. The belief in the arrival of a Ratu Adil is usually a form of opposition that arises naturally when a group of people experiences discrimination, oppression and social, cultural and political constraints. This Messianistic concept is usually in the form of predictions of the coming of a Savior. The following article tries to trace the figure of the Savior who is predicted to come by a king from Kediri who is quite well known and even he himself is also considered the Queen of Justice, namely Prabu Jayabaya.